ANALISA PENGARUH PERSENTASE CAMPURAN JARAK PAGAR (JATROPHA CURCAS) DAN KAPOK (CEIBA PETANDRA) BIODIESEL TERHADAP PERUBAHAN SIFAT BAHAN BAKAR - Dharma Surya; Sebayang Rihat (ROTOR, 2018)
To increase the production of biodiesel from non-edible vegetable oils, it is one of the effective ways to solve the limited number of traditional raw materials and the high prices of these raw materials. The primary objective of this study was to optimize the production of biodiesel derived from non-edible raw materials, namely J. curcas and C. Pentandra. The production process is carried out through the esterification and transesterification process of the mixture of J. curcas and C. Pentandra oils. The results of the study indicate a change in biodiesel properties due to the mixing of raw materials. But overall, the mixture of J. curcas and C. Pentandra oils have characteristic features that are suitable and meet the requirements given in the D6751 ASTM and EN 14214 standards. Keywords: alternative fuels; optimization; non-edible oil; biodiesel mixture